AWARENESS AND KNOWLEDGE OF GASTROINTESTINAL ULCERS AMONG RURAL FARMING HOUSEHOLDS IN ONDO STATE, NIGERIA - Akintade, Taiwo Folajimi (FUDMA JOURNAL OF SCIENCES, 2025)
Awareness and knowledge of gastrointestinal ulcers among rural farming households are critical aspects of public health that can influence both prevention and early intervention strategies. Thus this study was conducted to assess the awareness and knowledge of rural farming household to gastrointestinal ulcer in Ondo State Nigeria. A multistage sampling technique was used in the selection of one hundred and twenty respondents for the study. Frequency counts, percentages, mean and regression analysis were used in analyzing the data for the study. Primary data for the study was collected with a questionnaire coupled with an interview schedule. The mean age of the respondents was 47 years. Majority (63.32%) of the respondents were males. The mean farming experience was 6 years. Mean farming household size was 8 while majority were married. The respondents also had a mean farm size of 4 hectares. The level of awareness and knowledge was relatively low. Also majority (70.3%) sourced their information from Co Farmers while the perception of the respondents was fairly moderate. The regression analysis showed that only means of information was not significant to the level of awareness of respondents to gastrointestinal ulcer. The study concludes that awareness and knowledge levels are low, necessitating targeted health education programs to improve rural household health outcomes. The study recommends that community health education program should be organized to teach rural household farmers about the causes, symptoms and treatment of gastrointestinal ulcer in the study area.